Family Types and Political Development - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2020)
Many years ago, Emmanuel Todd argued that differences in family organization - specifically the rules of inheritance, the number of generations living under one roof, and endogamous marriage - are reflected in the organization of the state. He also argued that different family types lead to different paths of economic development. Economists have long ignored these sweeping claims, but with increasing interest in the deep causes of economic development, family types have caught the attention of some economists. Here, we try to take Todd seriously and evaluate his predictions empirically. Relying on a parsimonious model with exogenous covariates, we find mixed results. On the one hand, countries in which authoritarian family types dominate have much higher levels of the rule of law and innovation than predicted by Todd. On the other, countries in which the communitarian family types dominate are characterized by racism, low levels of the rule of law, few checks on government, and late industrialization. Countries in which endogamy is frequently practiced display a high level of state fragility and have weak civil society organizations.
Keywords: D10; H11; J12; K36; N30; O17; Z12; 330; Family types; family systems; family structures; ideology; state formation; constitutional structure; economic development